ARTIFICIAL INTELLIGENCE AND ITS EFFECT ON NIGERIAN YOUTH IN THE 21STCENTURY - BOLARINWA ADEBAYO OLUWASEGUN; OJEDIRAN SUNDAY ABEL (International Studies Journal)
The world advancement in the 21st century is highly commendable and aimed at making human endeavours very easy to achieve. The various advancements hinges on the technological development which has been revealed in various means and format which as a matter of emphasis have led to a crescendo which is the recent spread of Artificial Intelligence (AI). It is aimed at setting ease for human endeavours, but a call for concern as aimed in this paper is the relevance of AI in the Nigerian context in light of various challenges among Youths in the contemporary time. Creating answer to the question of necessity and validity of AI in the Nigerian setting will go a long way to encourage or discourage the emphasis on adopting it hook, line and sinker. Studies on AI have mostly been channelled towards the positive effect on the society at large but this study strikes a new path of examining the usage among youths. Therefore, using evaluation research method which considers the AI phenomenon in Nigerian context, this work weighs the effect of AI on Nigerian youths and observes that it has more tendency of complicating poverty if not properly handled by the leaders of the country. As such, the study recommends that, proper education be made available for the usage, and less emphasis should be placed on the usage in industries where human services are needed.